Semiotika Makna Pesan Cover Album PErmission to Dance Boyband BTS - Megawati, Eka; Yuniastarani, Nandha Dwi (Jurnal Mahardika Adiwidia, 2022)
The purpose of this study was to understand the Semiotics of the Meaning of the Album Cover â€œPermission to Danceâ€ by Boyband BTS. The theory used is Charles Sanders Peirce's Theory of Semiotics. As for Research methods used on this research is Semiotic Analysis with qualitative approach. The results of the study found that each visible sign on the album cover has a deep meaning, not only does it show the bright colors such as orange, purple, black, blue, and even the writing font, the shapes, they were an icon that symbolize meaning which could be interpret differently, depending on who, whom or whose see and read the meaning behind. BTS tried to send message through their album, not just the music, even the cover of the album is full of symbols with meanings.